PHP and MySQL web development - Welling, Luke, 1972- (Developer's library., 2017)
"PHP and MySQL are popular open-source technologies that are ideal for quickly developing database-driven Web applications. PHP is a powerful scripting language designed to enable developers to create highly featured Web applications quickly, and MySQL is a fast, reliable database that integrates well with PHP and is suited for dynamic Internet-based applications. PHP and MySQL Web Development shows how to use these tools together to produce effective, interactive Web applications. It clearly describes the basics of the PHP language, explains how to set up and work with a MySQL database, and then shows how to use PHP to interact with the database and the server. This practical, hands-on book consistently focuses on real-world applications, even in the introductory chapters. The authors cover important aspects of security and authentication as they relate to building a real-world website and show you how to implement these aspects in PHP and MySQL. They also introduce you to the integration of front-end and back-end technologies by using JavaScript in your application development. The final part of this book describes how to approach real-world projects and takes the reader through the design, planning, and building of several projects. The fifth edition of PHP and MySQL Web Development has been thoroughly updated, revised, and expanded to cover developments in PHP through versions 5.6 and 7, as well as features introduced in recent stable releases of MySQL,"--Amazon.com.